Exploring possible benefits of Litsea cubeba Pers. extract on growth, meat quality, and gut flora in white-feather broilers - Luo, Yankai; Bi, Yuchen; Xu, Ziyun; Shan, Linxian; He, Jun; Wang, Kedan; Zhou, Zhengjiang; Yu, Lihui; Jiang, Xingjiao; Yang, Jiangrui; Yu, Lijun; Gao, Rui; et al. (Frontiers in Veterinary Science, 2024)
White-feather broiler chickens are the dominant species in global poultry meat production. Yet there is growing concern about their health, quality, and growth efficiency. While feed additives, often antibiotics or synthetic chemicals, are used to maintain the health of the animals, drug resistance limits their use. Litsea cubeba (Lour.) Pers., a traditional Chinese herb with antibiotic-like benefits but without the risk of drug resistance, has not yet been explored as an additive to broiler diets. In the present study, broilers of the AA+ hybrid strain were randomly divided into three groups of 16: a control group (regular feed), a low-dose group (1.25 g/kg added L. cubeba extract), and a high-dose group (2.50 g/kg added L. cubeba extract). After 35 days, we found that the extract had no effect on growth. However, gut flora analysis revealed that both doses of the extract had a positive influence on amino acid content and minor unsaturated fatty acids, thus improving the flavor and nutritional value of the meat These findings suggest that L. cubeba extract, at either dose, could serve as a sustainable alternative to antibiotics, thus reducing the risk of drug resistance while improving meat quality, nutrition, and flavor.